Strengthening Organizational Culture Through Transformational Leadership Model - Auliyaur Rokhim (Journal of Innovative Islamic Education Management, 2025)
The transformation of the public relations role in crisis communication has become a strategic issue. A strong organizational culture is an essential factor in improving the quality of education and shaping the character of students in Islamic educational institutions. At MI Raudlatul Ulum, challenges still exist regarding the consistency of implementing Islamic values, teacher involvement in learning innovation, and suboptimal internal communication and collaboration. This study aims to analyze strategies for strengthening organizational culture through transformational leadership as an effort to enhance teacher professionalism, learning quality, and student character development. The research employs a qualitative approach with a case study design, involving participatory observation, in-depth interviews with the principal, teachers, and staff, as well as documentation of school activities. Data analysis was conducted thematically to identify strategies, challenges, and the impact of organizational culture strengthening. The findings show that the implementation of transformational leadership through strengthening the school’s vision and mission, fostering Islamic morals and values, mentoring and empowering teachers, collaboration-based management, establishing effective communication systems, value-based performance evaluation, and recognition of active participation can reinforce a harmonious, productive, and Islamic organizational culture. These strategies increase the motivation, engagement, and loyalty of teachers and staff while creating a conducive learning environment for students. The implications of this study indicate that transformational leadership can serve as an effective model for other Islamic educational institutions in building a sustainable school culture oriented toward moral values, ethics, and academic achievement.